MAMMAL SURVEY IN SONG HINH PROTECTED FOREST, PHU YEN PROVINCE, VIETNAM - A. V., Abramov; S. V. , Kruskop; Dinh, The Dung; Vu, Dinh Duy (Tạp chí Khoa học và Công nghệ nhiệt đới, 2025)
Rapid field surveys of mammals in the Song Hinh Protected Forest (Phu Yen Province, Vietnam) were conducted in January and June 2021. Thirty-four small mammals were recorded based on field observations and on morphological and/or molecular evidence: two Scandentia species, three Eulipotyphla species, three Carnivora species, 10 Rodentia species and 16 Chiroptera species. The results of the present study confirm the wealth and diversity of small mammals in the studied area. Undoubtedly, Song Hinh Protected Forest is worth having higher conservation status, like a Nature Reserve.